Development of behaviour change communication model for improving male participation in maternal and child health services among Saharia Tribes in Gwalior district of Madhya Pradesh: a mixed method approach - Adhikari, Tulsi; Gulati, Bal Kishan; Juneja, Atul; Nair, Saritha; Rao, M. V. Vardhana; Sharma, Ravendra Kumar; Saha, Kalyan B.; Singh, Shalini (International Journal Of Community Medicine And Public Health, 2020)
Background: Behaviour of men, their beliefs and attitudes affect the maternal health outcomes of women and their babies. The exclusion of men from maternal health care services could lead to few women seeking maternal health services. A study was conducted for development of a Behaviour change communication (BCC) model for improving the male participation in utilization of maternal and child health services among Saharia tribes of Gwalior district of Madhya Pradesh and to assess its feasibility. Methods: Mixed method approach, both quantitative and qualitative, were used in the study. Couple interviews were conducted to assess the level of maternity care services utilization and level of male participation in maternity care. Focused Group Discussions (FGDs) and Key informants’ Interviews (KIIs) were conducted to assess the community perspective and barriers of male participation. In the exploratory phase, there were couple interviews, key informant interviews and focus group discussions and data analysis, followed by development of a Behavior Change Communication (BCC). Feasibility of the model was assessed through three principles, i.e., acceptance, integration with the current programme and short term impact of BCC. Results: Based on the findings of couple interviews, FGDs and KIIs, a BCC model was developed to improve the male involvement in maternal and child health and its feasibility was assessed. Conclusions: The developed BCC model went successfully through the three principles of the feasibility and therefore it can be implemented in Saharias for improving the male participation in maternity care and for improving the utilization of maternity care services.